(untitled) (Journal of Natural Language and Linguistics, 2024)
The study aims to identify the mediating effect of reading attitude on the relationship between motivation and academic performance among students in the Filipino subject. Stratified random sampling was used to identify 333 students in grade 11 from three selected private institutions in Davao City, Davao del Sur, Region XI. The study used a quantitative research design and applied a descriptive-correlation technique. Meanwhile, the adopted survey questionnaire was validated and used to gather the data needed to conduct the study. Results revealed through weighted mean that the level of motivation and reading attitude among students in the Filipino subject were high while the academic performance rated very high. With the help of regression analysis, results proved that there was a significant relationship among variables. Thus, the med graph result showed that the last step was significantly reduced and remained significant, and partial mediation was achieved, which suggested that motivation and academic performance among students in the Filipino subject were mediated by the reading attitude. These findings indicate that students with high levels of reading attitude helped increase the level of motivation and improve the academic performance among students in the Filipino subject. Therefore, students will be more motivated. Students, school management, teachers, and institutions can use these findings to understand, support, and make interventions for the improvement of academic performance among students in the Filipino subject.